Implementasi Nilai-Nilai Fikih Kontemporer Dalam Kurikulum Pendidikan Islam Berbasis Moderasi Beragama - Riki Faisal; Neneng Nurhasanah; Gina Kania; Hasan Al Banna; Vina Febiani Musyadad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic education today faces the challenge of developing a generation that is moderate, tolerant, and responsive to changing times. This study aims to examine the implementation of contemporary Islamic jurisprudence values in the Islamic Education curriculum based on religious moderation at the elementary school level. The background of this study is based on the importance of presenting religious learning that is contextual, inclusive, and based on the values of benefit. The approach used was a qualitative case study method, located at SDIT Kasih Ibu, East Karawang District. Data collection techniques included in-depth interviews, participatory observation, and document analysis involving teachers, the principal, and students. The results of the study indicate that contemporary Islamic jurisprudence values such as empathy, social justice, tolerance, and responsibility have been integrated into learning through contextual strategies and habituation practices in the school environment. Teachers play a central role in inserting these values into lesson plans and learning activities without having to express them in formal Islamic jurisprudence terminology. In conclusion, the implementation of contemporary Islamic jurisprudence values in elementary education can be effective through a reflective, participatory, and character-based approach, which is in line with the spirit of religious moderation in Islamic education. The implication is that Islamic education needs to be directed at strengthening a contextual and humanistic value-based curriculum from the elementary level.